RETRACTED: Technical performance of Plant Clinics as providers of crop protection services: The case of Guilan Province, Iran. (November 2017) - Azimi, Roya; Allahyari, Mohammad S.; Damalas, Christos A.; Kavoosi-Kalashami, Mohammad
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Chair Editor. After a thorough investigation, the Editor has concluded that the acceptance of this article was partly based upon the positive advice of one illegitimate reviewer report. The report was submitted from an email account which was provided by the corresponding author C.A. Damalas as a suggested reviewer during the submission of the article. Although purportedly a real reviewer account, the Editor has concluded that this was not of an appropriate, independent reviewer. This manipulation of the peer-review process represents a clear violation of the fundamentals of peer review, our publishing policies, and publishing ethics standards. Apologies are offered to the reviewer whose identity was assumed and to the readers of the journal that this deception was not detected during the submission process.